An epidemiological study of mental disorders at Pune, Maharashtra - Balbir S Deswal; A Pawar (Wolters Kluwer Medknow Publications, 2012)
Background: The WHO Global Burden of Disease study estimates that mental and addictive disorders are among the most burdensome in the world, and their burden will increase over the next decades. The mental and behavioral disorders account for about 12% of the global burden of disease. However, these estimates and projections are based largely on literature review rather than cross-national epidemiological surveys. In India, little is known about the extent, severity and unmet need of treatment mental disorders. Thus, there was a need to carry out rigorously implemented general population surveys that estimate the prevalence of mental disorders among urban population at Pune, Maharashtra. The study attempted to address unmet need and to form a basis for formulating the mental health need of the community. Objective: The study was undertaken to estimate the lifetime prevalence and 12 month prevalence of specific mental disorders in urban population, socio-demographic correlates of mental disorders and to assess the service utilization in individuals with mental disorders. Materials and Methods: The study was undertaken among adults aged 18 years and above living in house hold and in geographical area of Pune , Maharashtra. A minimum sample of 3000 completed interviews was planned using representative probabilities to population size (PPS) sampling method which ensured equal probability for every eligible member. Data listing was obtained from Census Office from recent census of 2001 data. The face to face interviews were undertaken in homes using fully structured interview schedule of World Mental Health Survey Initiative duly revised Version of WHO- Composite International Diagnostic Interview (CIDI 3.0) by trained investigators. Clinical reappraisal was carried out using Schedules for Clinical Assessment in Neuropsychiatry (SCAN) among ten percent of diagnosed cases selected randomly. Data were entered into DDE (Blaize Software) and analyzed using SPSS software package. Results: Overall lifetime prevalence of mental disorders was found to be 5.03%.Rates among males (5.30%) were higher as compared to females (4.73%). Among the diagnostic group , depression(3.14%) was most prevalent followed by substance use disorder (1.39%) and panic disorder (0.86%). Overall 12 month prevalence of mental disorder was found to be 3.18% which was 3.47% among males and 2.85% among females. Prevalence of depression (1.75%) was the most 12-month mental disorder, followed by substance use mental disorder (0.99%) and panic disorder (0.69%).Lifetime and twelve month prevalence of any mental disorder was the highest among employed group, followed by home makers and depression was more among married, followed by separated/divorced/widowed group and the least in unmarried group in the study. Treatment gap due to low prescription received indicated the most of the ill person did not acknowledge their need for treatment or do not received the appropriate care. Conclusion: The figure of 5.03% prevalence of diagnosable psychiatric disorders in adult population points to the great need to increase the prevention strategies both at primary and secondary level to overcome the disability and economic loss to society due to mental disorders.